Potential Involvement of Protein Phosphatase PPP2CA on Protein Synthesis and Cell Cycle During SARS-CoV-2 Infection: A Meta-Analysis Investigation - Luca P. Otvos; Giulia I. M. Garrito; Gabriel E. Jara; Paulo S. Lopes-de-Oliveira; Luciana E. S. F. Machado (Kinases and Phosphatases)
Coronavirus disease 2019 is a multi-systemic syndrome that caused a pandemic. Proteomic studies have shown changes in protein expression and interaction involved in signaling pathways related to SARS-CoV-2 infections. Protein phosphatases play a crucial role in regulating cell signaling. In this study, we assessed the potential involvement of protein phosphatases and their associated signaling pathways during SARS-CoV-2 infection by conducting a meta-analysis of proteome databases from COVID-19 patients. We identified both direct and indirect interactions between human protein phosphatases and viral proteins, as well as the expression levels and phosphorylation status of intermediate proteins. Our analyses revealed that PPP2CA and PTEN are key phosphatases involved in cell cycle and apoptosis regulation during SARS-CoV-2 infection. We also highlighted the direct involvement of PPP2CA in the cell division throughout its interaction with CDC20 protein (cell division cycle protein 20 homolog). This evidence strongly suggests that both proteins play critical roles during SARS-CoV-2 infection and represent potential targets for COVID-19 treatment.